2021
DOI: 10.1101/2021.06.23.449663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An empirically-driven guide on using Bayes Factors for M/EEG decoding

Abstract: Bayes Factors can be used to provide quantifiable evidence for contrasting hypotheses and have thus become increasingly popular in cognitive science. However, Bayes Factors are rarely used to statistically assess the results of neuroimaging experiments. Here, we provide an empirically-driven guide on implementing Bayes Factors for time-series neural decoding results. Using real and simulated Magnetoencephalography (MEG) data, we examine how parameters such as the shape of the prior and data size affect Bayes F… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…For all comparisons, we used the BayesFactor package in R (Morey et al, 2018). Following recommendations in Teichmann et al (2021), we used a JZS prior (Rouder et al, 2009) with a scale factor of 0.707. This is the default prior and scaling in the BayesFactor package because it makes minimal assumptions about the expected effect size, and serves as a "non-informative default" (Rouder et al, 2009, p. 232).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all comparisons, we used the BayesFactor package in R (Morey et al, 2018). Following recommendations in Teichmann et al (2021), we used a JZS prior (Rouder et al, 2009) with a scale factor of 0.707. This is the default prior and scaling in the BayesFactor package because it makes minimal assumptions about the expected effect size, and serves as a "non-informative default" (Rouder et al, 2009, p. 232).…”
Section: Discussionmentioning
confidence: 99%
“…For decoding analyses, we used a series of t-tests using the ttestBF function (Morey et al, 2018) from the BayesFactor package with the parameters described above. The alternate hypothesis is that the decoding is above chance (50%), and the null-interval was effect sizes from negative infinity up to 0.5, as effect sizes during baseline periods prior to stimulus onset from previous work have shown this to be most appropriate (Teichmann et al, 2021). This formed a one-sided hypothesis that the effect size for alternate hypothesis should be positive.…”
Section: Discussionmentioning
confidence: 99%
“…We used a point-nil for the null-hypothesis and specified a half-Cauchy prior for the alternative hypothesis with medium width (r = 0.707) that covered an interval with effect sizes ranging from 0.5 to infinity. We chose this prior range because previous studies that looked at visual decoding found effect sizes as large as 0.5 during a baseline period when there cannot be any meaningful information in the signal 49 . We also performed a robustness check with a wide (r = 1) and ultrawide ( r = 1.414) prior which did not have a pronounced effect on the results.…”
Section: Methodsmentioning
confidence: 99%
“…We used a half-Cauchy prior with medium width (r = 0.707) and adjusted the prior range of the alternative hypothesis from 0.5 to infinity to allow for small effects under the alternative hypothesis (Rouder et al, 2009). We chose this prior range because previous studies using visual decoding found effect sizes as large as 0.5 during a baseline period when there cannot be any meaningful information in the signal (Teichmann et al, 2021). We also performed a robustness check with a wide (r = 1) and ultrawide (𝑟 = 1.414) prior which did not have a pronounced effect on the results.…”
Section: Statistical Inferencementioning
confidence: 99%
“…We used Bayesian statistics to determine the evidence for the alternative hypothesis of non-zero correlations (across the 16 participants) and the null hypothesis of no correlation for each point in time (Dienes, 2011;Kass and Raftery, 1995;Rouder et al, 2009a;Teichmann et al, 2021;Wagenmakers, 2007), using the Bayes Factor R package (Morey and Rouder, 2018). The prior for the null hypothesis was set at zero.…”
Section: Statistical Inferencementioning
confidence: 99%